Good day ~_~ /////////////
Answer
The number of followers is decreasing
Step-by-step explanation:
The function is decreasing over time since the base of the exponent is less than 1. The value is greater when t is 0 and decreases as t increases.
Answer:
x-3
Step-by-step explanation:
f(x) = 3x – 2
g(x) = 2x + 1
(f – g)(x) = 3x-2 - ( 2x+1)
Distribute the minus sign
= 3x-2 -2x -1
= x -3
0=0 because first you have to rearrange the terms then distribute after you have to subtract the numbers then combine like terms and once again rearrange terms I’ll add a pic to help
You can get all the terms on one side, and then solve for x by any means:
![0 = -8x^2+22x+6](https://tex.z-dn.net/?f=0%20%3D%20-8x%5E2%2B22x%2B6)
Factor out a -2:
![0 = -2(4x^2-11x-3)](https://tex.z-dn.net/?f=0%20%3D%20-2%284x%5E2-11x-3%29)
Factor this equation:
![0 = 4x^2-11x-3](https://tex.z-dn.net/?f=0%20%3D%204x%5E2-11x-3)
I will use the AC method. To use it, first multiply a and c (in ax^2 + bx +c):
![4*-3 = -12](https://tex.z-dn.net/?f=4%2A-3%20%3D%20-12)
Now, look for two numbers that multiply to -12 and add to -11. Obviously these numbers are -12 and 1. (-12*1 = -12 and -12+1 = -11). Now, because of rules, you set it up in a Punnett square:
4x^2 -12x
x -3
Now, we find common factors of the terms in rows:
_x_______-3__
4x| 4x^2 -12x
1 | x -3
So, you can use this to write an equivalent expression to the quadratic given:
![(x-3)(4x+1)](https://tex.z-dn.net/?f=%28x-3%29%284x%2B1%29)
Now, we known the factors are (solve for x):
3 and -1/4.